Single synonymous mutation in factor IX alters protein properties and underlies haemophilia B. Issue 5 (22nd December 2016) - Simhadri, Vijaya L; Hamasaki-Katagiri, Nobuko; Lin, Brian C; Hunt, Ryan; Jha, Sujata; Tseng, Sandra C; Wu, Andrew; Bentley, Amber A; Zichel, Ran; Lu, Qi; Zhu, Lily; Freedberg, Darón I; et al.
Abstract : Background: Haemophilia B is caused by genetic aberrations in the F9 gene. The majority of these are non-synonymous mutations that alter the primary structure of blood coagulation factor IX (FIX). However, a synonymous mutation c.459G>A (Val107Val) was clinically reported to result in mild haemophilia B (FIX coagulant activity 15%–20% of normal). The F9 mRNA of these patients showed no skipping or retention of introns and/or change in mRNA levels, suggesting that mRNA integrity does not contribute to the origin of the disease in affected individuals. The aim of this study is to elucidate the molecular mechanisms that can explain disease manifestations in patients with this synonymous mutation. Methods: We analyse the molecular mechanisms underlying the FIX deficiency through in silico analysis and reproducing the c.459G>A (Val107Val) mutation in stable cell lines. Conformation and non-conformation sensitive antibodies, limited trypsin digestion, activity assays for FIX, interaction with other proteins and post-translation modifications were used to evaluate the biophysical and biochemical consequences of the synonymous mutation. Results: The Val107Val synonymous mutation in F9 was found to significantly diminish FIX expression. Our results suggest that this mutation slows FIX translation and affects its conformation resulting in decreased extracellular protein level. The altered conformation did not change the specific activity of the mutated protein. Conclusions: The pathogenic basis for one synonymous mutation (Val107Val) in the F9 gene associated with haemophilia B was determined. A mechanistic understanding of this synonymous variant yields potential for guiding and developing future therapeutic treatments.